A new, conspicuously coloured snapping shrimp from the north-western Indian Ocean (Malacostraca: Decapoda: Alpheidae: Alpheus) - Arthur Anker (Papéis Avulsos de Zoologia)
Abstract A new, brightly coloured and morphologically distinctive species of the alpheid genus Alpheus Fabricius, 1798 is described based on a single female specimen collected in shallow waters of Masirah Island, Oman. Alpheus sarapis sp. nov. appears to be morphologically somewhat intermediate between the A. leviusculus Dana, 1852, A. edwardsii (Audouin, 1826) and A. paracrinitus Miers, 1881 species groups, although the presence of slight sinuses on the major chela palm suggests that it may be a derived member of either of the former two groups.